Conservative Surgery to Approach Odontogenic Keratocyst in Young Patient: Case Report - Almeida, Lorena Mendes; Sol, Izabella; Rodrigues, Cristóvão Marcondes de Castro; Souto, Lucas Augusto Pereira; Zanetta-Barbosa, Darceny; Silva, Claudia Jordão (ARCHIVES OF HEALTH INVESTIGATION, 2024)
The odontogenic keratocyst consists of a benign lesion of the oral cavity that involves peculiarities regarding its growth, treatment, and prognosis. The main objective in the treatment of this pathology is to guarantee small morbidity to the patient and to reduce recurrences, which are characteristic of this type of injury. In this case report, we demonstrate the effectiveness of less invasive treatments for smaller-sized lesions that responded well to cystic decompression. A 33-year-old female, diagnosed with odontogenic keratocyst in the region of the angle and left mandibular ramus, was surgically treated by five months of marsupialization and subsequent enucleation with a 30-month follow-up without relapsing. The diagnosis of this pathology is performed through radiographic and histopathological exams associated with clinical findings. Due to the slow asymptomatic growth, the identification of the keratocyst is often made lately, and a radical treatment can promote functional and esthetic deficiencies. Even with favorable results of conservative treatment, long-term follow-up should be performed to detect possible relapses.